1) pi/2 < a < pi, поэтому sin a > 0, cos a < 0 cos a = -√6/4; cos^2 a = 6/16 sin^2 a = 1 - cos^2 a = 1 - 6/16 = 10/16; sin a = √10/4 tg a = sin a / cos a = (√10/4) : (-√6/4) = -√10/√6 = -√5/√3 = -√15/3
2) 0 < a < pi/2, поэтому sin a > 0, cos a > 0 sin a = √2/3; sin^2 a = 2/9 cos^2 a = 1 - sin^2 a = 1 - 2/9 = 7/9; cos a = √7/3 tg a = sin a / cos a = (√2/3) : (√7/3) = √2/√7 = √14/7
3) 3pi/2 < a < 2pi, поэтому sin a < 0, cos a > 0 cos a = 15/17; cos^2 a = 225/289 sin^2 a = 1 - cos^2 a = 1 - 225/289 = 64/289; sin a = -8/17 tg a = sin a / cos a = (-8/17) : (15/17) = -8/15
3/(2^(2 - x²) -1)² - 4/(2^(2- x²) -1) + 1 ≥ 0 ;
замена : t = 2^(2-x²) -1
3 / t² - 4 / t +1 ≥ 0 ;
(t² - 4t +3) / t² ≥ 0
для квадратного трехчлена t² - 4t +3 t₁=1 корень: 1² - 4*1+3 = 1- 4+3 =0.
t₂ =3/t₁=3/1=1 (или t₂ =4 -1=3)
* * * наконец можно и решить уравнение t² - 4t +3=0 * * *
(t² - 4t +3) / t² ≥ 0 ⇔ (t -1)(t - 3) / t² ≥ 0 .
+ + - +
(0) [1] [ 3]
* * * совокупность неравенств [ { t ≤ 1 ; t ≠0 . { t ≥ 3 * * *
a)
{ 2^(2-x²) -1 ≤ 1 ; 2^(2-x²) -1 ≠ 0 .⇔ { 2^(2-x²) ≤ 2 ; 2^(2-x²) ≠ 1 . ⇔
{ 2^(2-x²) ≤ 2¹ ; 2^(2-x²) ≠ 2⁰.⇔ {2-x² ≤ 1 ; 2 - x² ≠ 0.⇔{ x² -1 ≥ 0 ; x² ≠ 2⇔
{ (x+1)(x-1) ≥ 0 ; x ≠ ±√2 . ⇒ x∈ ( -∞ ; -√2 ) ∪ (-√2 ; -1] ∪ [1 ; √2) U (√2 ; ∞) .
b)
2^(2-x²) -1 ≥ 3 ⇔ 2^(2-x²) ≥ 4 ⇔2^(2-x²) ≥ 2² ⇔2- x² ≥ 2 ⇔ x² ≤ 0 ⇒ x=0.
ответ: x∈ ( -∞ ; -√2 ) ∪ (-√2 ; -1] ∪ { 0} ∪ [1 ; √2) U (√2 ; ∞) .